A guide to JES3 to JES2 migration - Fadel, Luiz; Furuya, Nobuhiko; Kuehner, Lutz; Paranhos, Ricardo (IBM redbooks., 2018)
Abstract This IBM® Redbooks® publication provides information to help clients that have JES3 and want to migrate to JES2. It provides a comprehensive list of the differences between the two job entry subsystems and provides information to help you determine the migration effort and actions. This book considers the features of JES2 as available on releases of IBM z/OS® V2R2 and V2R3. It should be used with JES3 to JES2 Migration Considerations, SG24-8083. This publication is divided into three parts: Part 1, "Planning to migrate from JES3 to JES2" on page 1, gives you information to make the decision and plan your migration. Part 2, "Use Case Study" on page 85, provides a Use Case Study based on an actual customer experience in a successful migration. Part 3, "Appendixes" on page 153, provides an appendix with sample tools that can help the migration process and exploitation of some of the new JES2 functions. This book is aimed at operations personnel, system programmers, and application developers